Use of forest land for national-priority infrastructures in Nepal - Sharma, U. R. (Banko Janakari, 2017)
Forest conversion has been identified as one of the several bottlenecks affecting upon the major infrastructure projects in Nepal, especially in the energy and transport sectors. Nepal’s policy requires at least 40% of its land cover under forest. This means if any forest land is converted to non-forest land, it must be compensated with an equivalent area, preferably in the similar ecotype in the nation. In addition, a specified number of trees must be planted for the number of trees felled in the project site, and the site must be managed and protected for five years by the developers. These provisions have led to growing resentment between the developers and the Ministry of Forests and Soil Conservation (MFSC), leading to delay in providing forest lands for infrastructure projects. With a view to develop mechanisms for the government to rapidly provide forest land for nationally important infrastructure projects, the Government databases were examined to analyze the forests handed over to the developers for non-forestry uses. The data showed that a total of 14,028.4 ha of forest area were handed over to the developers for non-forestry uses until the end of 2015. On an average, 263.8 ha forest area was found to be handed over to the developers between the period of 2010–2013. However, there is a declining trend of forest handed over for non-forestry purposes in the recent years. The decline could be due to the strict enforcement of the legal provision which limits the conversion of forest areas to non-forest areas except in the case of the “national priority projects”. It has been recommended that the conversion of forest for infrastructure development should be examined with a holistic perspective by taking all the related components of forest conversion into consideration, from providing forest land for replacement planting. It is recommended that the Forest Product Development Board (FPDB), a parastatal organization under the MFSC, should be entrusted with the work of plantation related to forest conversion. The fund for this work should flow directly from the developers to the FPDB. The possibility of forming a land bank to facilitate the work of the FPDB is also recommended. Banko Janakari, Vol. 27, No. 1, Page: 60-64